PENINGKATAN AKTIVITAS DAN HASIL BELAJAR IPA DENGAN MODEL KOOPERATIF TIPE THINK PAIR SHARE DI KELAS VI SDN 15 PAKASAI KECAMATAN PARIAMAN TIMUR - Agustrinaldi Agustrinaldi (FIP Unimed, 2016)
ABSTRACT The background of the problem in this research was the students seemed to be less active in the learning process as the class was dominated by the teacher. So that it caused very minimal student activity and student learning outcomes is low. This research was aimed to improve learning outcomes IPA with cooperative models type think of pair share in class VI SDN 15 Pakasai. The results showed that in the first cycle, the overall activity of students scored an average of 51,3, in the second cycle increased to 81,6. From an average cognitive aspects of student learning result in the first cycle got 70 score on the second cycle increased to 88. Affective aspects in the first cycle get an average value of 50,5 and in the second cycle value of 80,2. Psychomotor aspects of the first cycle get an average value of 58,6 in the second cycle increased to 92,3. Based on these result, it was concluded that the use of cooperative model tps type can increase the activity and learning outcomes of sixth grade students of SDN 15 Pakasai Pariman city. Keywords: Cooperative Type Think-Pair-Share Results Learning, Student Activities